EVALUATION OF THE THERAPUTIC EFFICACY OF COMPUTED TOMOGRAPHY GUIDED PERIRADICULAR THERAPY IN PATIENTS WITH EXTRAFORAMINAL DISC HERNIATIONS - Veljanovski, Dimitar Vasko; Prgova, Biljana; Kostova, Masha; Kostov, Milenko; Dodevski, Ace (Journal of Morphological Sciences, 2020)
Periradicular therapy (PRT) is a minimally invasive radiological technique for treatment of chronic lumbar pain.The aim of this study was to investigate the efficacy of PRT in patients with chronic lumbar pain and radiculopathy due to extraforaminal disc herniation. The study included a prospective follow-up of 30 patients with chronic lumbar pain and radiculopathy. All patients underwent magnetic resonance imaging (MRI) and extraforaminal neuro-radicular conflict was detected. The degree of pain intensity was scored according to the VAS scale. The degree of improvement was presented as excellent (over 75%), good (50 -70%), intermediate (25-49%) and poor (less than 25%). Functional and working status was rated according to Oswestry Disability index2.0 (ODI). Follow-up of treated patients was at 2 weeks and 3 months. After 2 weeks the improvement was excellent in14 patients (47%), good in 7 patients (23%), moderate in 7 patients (23%) and mild in 2 patients (7%). Improvement after 3 months was excellent in 15 patients (50%), good in 7 patients (23%), moderate in 3 patients (10%) and poor in 5 patients (17%). The improvement of the functional status according to the ODI score was at least 40% in 73.3% of patients after 2 weeks and 86.5% of patients after the third month. CT controlled PRT in patients with lumbar radiculopathy is a safe and effective procedure leading to a significant pain reduction and a better quality of life after the procedure. Keywords : epidural, steroid, lumbar, spine, radicular